Influence of cognitive and motor abilities on the level of current functioning in people with multiple sclerosis - Slavkovic Sanela; Golubovic Spela; Vojnovic Matilda; Nadj Congor (Sciendo, 2019)
Multiple sclerosis (MS) results in a wide range of disabilities. The effects of cognitive and motor dysfunctions are significant and affect level of functioning in people with MS.